2016
DOI: 10.1111/ijlh.12520
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of α‐thalassaemia variants using droplet digital PCR

Abstract: In conclusion, ddPCR is an alternative method for rapid detection of alpha thalassaemia variants in Malaysia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…The data showed that ddPCR could precisely recognize the ΔF508-MUT CFTR allele in cffDNA of all proband fetuses and exclude unaffected control fetuses with high sensitivity and cost-effectiveness. In 2016, Lee et al detected both common and rare deletions in α thalassemia using ddPCR, which showed a detection limit of ~1 ng and a rapid detection of α thalassemia variants in a Malaysian population [45].…”
Section: Prenatal Diagnosis Of Genetic Diseasementioning
confidence: 99%
“…The data showed that ddPCR could precisely recognize the ΔF508-MUT CFTR allele in cffDNA of all proband fetuses and exclude unaffected control fetuses with high sensitivity and cost-effectiveness. In 2016, Lee et al detected both common and rare deletions in α thalassemia using ddPCR, which showed a detection limit of ~1 ng and a rapid detection of α thalassemia variants in a Malaysian population [45].…”
Section: Prenatal Diagnosis Of Genetic Diseasementioning
confidence: 99%
“…At present, the conventional methods to detect large deletional mutation in α-globin cluster include Multiplex ligation-dependent probe amplification (MLPA) [ 6 ], gap-Polymerase Chain Reaction (gap-PCR) [ 7 ] and droplet digital polymerase chain reaction (ddPCR) [ 7 9 ]. However, these methods have several limitations.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the conventional methods to detect large deletional mutation in α-globin cluster include MLPA [6] , gap-Polymerase Chain Reaction (gap-PCR) [7] and ddPCR [7][8][9] . However, these methods have certain limitations.…”
Section: Introductionmentioning
confidence: 99%